Formulation and Physical Evaluation of Green Tea Leaf Extract (Camellia Sinensis L.) As a Gel Peel Off Mask - Nadroh Br. Sitepu; Sri Widia Ningsih; Masyitoh Amaliyah Harahap (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Green tea contains flavonoids which are the result of metabolism of both plants which are widely distributed in plants. Catechins as the active substance in green tea leaves function as an antibacterial for Staphylococcus aureus which can inhibit the growth of acne. Gel peel off mask is a skin care preparation in the form of a gel and will dry after being applied to the skin. Peel off gel masks can be useful for repairing and treating facial skin from problems with wrinkles, aging, acne and can also be used to shrink pores. The purpose of this study was to determine the best formulation and concentration of green tea leaf extract peel-off gel masks. The research method used is an experimental method, by making a tea leaf extract formulation as a peel off gel mask. The results showed that the green tea leaf extract gel peel-off mask preparation was brown in color, had a distinctive smell, homogeneous and stable, did not irritate the volunteers' skin, and fulfilled the evaluation tests of other preparations. The preference test based on the preference parameter for texture is significant at 0.078 (sig=0.000<0.078), for color is significant at 0.05 (sig=0.000<0.05) and aroma is significant at 0.05 (sig=0.002<0.05). Green tea leaf extract with a concentration of 0.08%, 0.16% and 0.32% can be used as a gel peel off mask formulation. Future researchers are expected to be able to compare the effectiveness of peel off gel mask preparations with a variety of other types of tea and with different concentrations.Keywords: Green Tea, Mask, Peel Off